MOJOPURA WETAN, DESA PENYEBERANGAN DI DAERAH ALIRAN SUNGAI (DAS) BENGAWAN SOLO PADA MASA MAJAPAHIT? - Hari Lelono (Berkala Arkeologi, 2010)
Majapahit is a powerful kingdom which ruled Java from 12th to 15th century A.D. The kingdom was well known as the center of Javanese civilization with a tremendous influential power throughout the archipelago. Its capital was found in an area which had long been assumed as located in Trowulan District of Mojokerto Region in East Java. Archaeologists had long been assumed that the potential main access for entering the area were roads as well as rivers with Bengawan Solo as the most important one. Some old Javanese inscriptions mentioned the crossing-through villages lying over the river's edge which among them were Madanten, Wringin Wok and Bajrapura. Those village names could still easily be found until today, located over the edge of Bengawan Solo River in Gresik District. Mojopura Wetan is believed as an ancient village as mentioned in the inscription, identical to Bajrapura. Beside located close to Bengawan Solo, in the village was also found Hindu and Buddha statues. At present in the village could still be found the activity of local people using small boat to cross the river.